Sistem Pendukung Keputusan Pemilihan Mobil MPV Terbaik Menggunakan Metode MOORA - Guswandi, Dodi; Hafizh, M; Novita, Triana (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2026)
The selection of Multi-Purpose Vehicles (MPVs) at dealerships in Padang City involves complex and often conflicting criteria, where subjective recommendations risk leading to inaccurate decisions. This study aims to develop an objective decision support system to recommend the best MPV tailored to local needs by applying a Multi-Criteria Decision Making (MCDM) method based on the MOORA algorithm. Its primary contribution is a triple-perspective criteria model that integrates product technical aspects, local consumer preferences in Padang, and dealership business interests. Seven MPV alternatives were analyzed based on nine expert-weighted criteria. The optimization results identify the Honda BR-V as the top-ranking MPV, followed by the Mitsubishi X-Pander and Toyota Veloz. Validation using Spearman's Rank Correlation yielded a coefficient of ρ = 0.8036, confirming strong consistency with actual market performance. Thus, the MOORA method proves effective in generating accurate, objective recommendations for optimal MPV selection in Padang City.